2015
DOI: 10.1002/pc.23761
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of sisal fiber concrete cylinders externally wrapped with jute FRP

Abstract: The use of environmentally friendly natural fibers as building materials is benefit to achieve a sustainable construction. This article performs a study on the use of natural jute fibers as reinforcement of concrete and natural sisal fibers in fiber reinforced polymer (FRP) composites as concrete confinement, i.e. sisal fiber reinforced concrete (SFRC) composite column wrapped by jute FRP (JFRP) (SFRC-JFRP). Uniaxial compression test was conducted to assess the compression performance of the composite columns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Organic materials such as jute, sisal, coconut coir and date palm are among some of the alternatives that have been used to replace steel. However, the tensile capacity of these materials is often too low when compared with steel [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Organic materials such as jute, sisal, coconut coir and date palm are among some of the alternatives that have been used to replace steel. However, the tensile capacity of these materials is often too low when compared with steel [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been carried out on the use of natural materials instead of synthetic fiber materials, particularly as concrete confinement materials (Ghalieh et al, 2017;Tan et al, 2017;. In some of these studies, it has been stated that with two layers of flax fiber, the axial compressive strength was improved by 1.5 times and ductility by 8.5 times compared to unconfined concrete .…”
Section: General Informationmentioning
confidence: 99%
“…As stated by Hussain and Ali [7], the Jute fibers enhance crack resistance and toughness of concrete. According to Tan et al [8], the ultimate load of concrete columns has been increased by wrapping with JFRP composites. Alam and Al Riyami [9] showed that the toughness and strength of beams have been improved by the reinforcement using the natural fibers [10,11].…”
Section: Introductionmentioning
confidence: 99%